Towards comprehensive approaches in assessing NRM impacts: What we know and what we need to know - Swinton, S.M.; Shiferaw, B.; Freeman, H.A. (CAB International, 2005)
This chapter synthesizes the conceptual methodological and empirical issues for evaluating the impacts of natural resource management (NRM) technology and policy interventions. The intention is to highlight the salient features raised across the chapters and offer some insights on the key lessons, policy conclusions, knowledge gaps, and areas that need further research. Main topics of discussion include the state of the art in NRM impact assessment; integration of resource and environmental impacts into economic impact assessment; what we need to know - areas for future research. This include subtopics - how does NRM affect ecosystem functions and services, indicators of ecosystem performance, how to enhance attribution of impacts, can we properly value non-market ecosystem services, can the economic surplus approach be extended for integrated assessment, what do we know about economy wide impacts, simple steps toward better impact assessments, and institutionalising NRM impact assessment.